DAYA HAMBAT DAN DAYA BUNUH EKSTRAK SERBUK BATANG SIWAK TERHADAP BAKTERI STREPTOCOCCUS PYOGENES - NUGROHO EKO WIRAWAN BUDIANTO (Universitas Hang Tuah, 2020)
ABSTRACT Background: One of the most growing plants in the Middle East is siwak, which was used to clean teeth. Currently, we have toothpaste that contains siwak as its active ingredient. Previous studies have shown that siwak has anti-bacterial power on Streptococcus faecalis and Streptococcus mutans. This study aims to prove whether the extract of siwak stem powder can be used to inhibit the growth of Streptococcus pyogenes bacteria, one of which can cause pharyngitis. Methods: In this study, the Only Post Test Control Group Design method was used. This study used 24 samples divided into four repetitions (replications) and six treatments. The research used siwak stem extract at a concentration of 100%, 75%, 50% and 25%. Results: It was found that the zone of inhibition of siwak stem powder extract against the growth of Streptococus pyogenes. The mean inhibition zone of the concentrations of 100%, 75%, 50% and 25% was 10.77 mm, 9.77 mm, 8.47 mm and 0 mm. The results of statistical tests showed that the diameter of the bacterial inhibition zone in the K1 group was significantly different against K3, K4, K5, K6, and between the K2 groups against K3, K4, K5, K6 with Pvalue, <0.05. There is no significant difference between K1 and K2 and K3 with K4 and K4 with K5, because the value of Pvalue is> 0.05. Conclusion: The higher the concentration of siwak extract, the wider the inhibition zone will be. At a concentration of 50% the ethanol extract of the siwak stem powder can provide inhibitory power on the growth of the Streptcicoccus pyogenes bacteria. At concentrations of 75% and 100% the inhibition power also increased. At a concentration of 100% it was statistically significant different from the inhibition of amoxicillin.